Moving from classroom to clinic: evaluating academic preparation for clinical exercise physiologists in Canada. - Cook, Shawna; duManoir, Gregory R.; Sasso, John P. (Applied Physiology, Nutrition & Metabolism, 2026)
Clinical exercise physiologists (CEPs) play an essential role in delivering exercise-based interventions for individuals with chronic disease. While Canada's primary CEP certification, governed by the Canadian Society for Exercise Physiology (CSEP), outlines core competencies, the absence of program-level accreditation may lead to variability in academic preparation. This environmental scan evaluated the extent to which a subset of Canadian undergraduate programs align with CSEP-CEP certification requirements. Thirteen programs that participate in CSEP's Recommended Course Map initiative were examined from among 50+ kinesiology and exercise science programs operating nationally. Curricula were reviewed using structured coding of course content, skill assessment practices, and practicum integration. All programs demonstrated strong coverage of foundational knowledge; however, inconsistencies were observed in clinically-focused domains (e.g., health behaviour change, pharmacology), structured skill assessment, and supervised practicum experiences. Only 69% of programs included formal in-curriculum applied skill evaluations that directly address CSEP-CEP competency requirements, and 54% required a for-credit practicum. Practicum hours and settings varied widely, often falling short of national and international benchmarks. Findings highlight the need for stronger curriculum alignment, particularly in applied competencies and experiential learning. These results suggest that integrating structured, competency-based instruction and assessment across coursework and clinical placements would strengthen graduate readiness for both certification and clinical practice in healthcare contexts. This study provides timely insights to inform national CEP education standards and support strategic workforce planning as provinces expand CEP integration into healthcare systems.